2016
DOI: 10.1016/j.fertnstert.2015.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated leukemia inhibitory factor and its receptor regulated signal transducers and activators of transcription 3 pathway: a possible cause for repeated implantation failure in women with dormant genital tuberculosis?

Abstract: Our findings suggest that endometrium of women with dormant GTB is associated with poor receptivity, as evidenced by reduced receptivity markers and aberrant LIF-STAT3 signaling. In vitro treatment of hESC with HSP65 also confirms compromised endometrial decidualization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 57 publications
1
35
0
1
Order By: Relevance
“…PCR is a highly sensitive tool which has been successfully used for diagnosing GTB, even in the dormant form (Jindal 2006;Roy and Roy 2003;Bhanu et al 2005). Studies by Jindal et al (2012) and our group (Subramani et al 2016b) have shown that GTB-PCR can effectively diagnose dormant GTB in women when other conventional techniques fail to detect GTB in the endometrium. However, PCR is yet to be used reliably for the diagnosis of tuberculosis owing to the tendency of this technique to have false-positive or negative results.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…PCR is a highly sensitive tool which has been successfully used for diagnosing GTB, even in the dormant form (Jindal 2006;Roy and Roy 2003;Bhanu et al 2005). Studies by Jindal et al (2012) and our group (Subramani et al 2016b) have shown that GTB-PCR can effectively diagnose dormant GTB in women when other conventional techniques fail to detect GTB in the endometrium. However, PCR is yet to be used reliably for the diagnosis of tuberculosis owing to the tendency of this technique to have false-positive or negative results.…”
Section: Discussionmentioning
confidence: 96%
“…Even dormant tubercle bacilli may cause functional damage to the endometrium and affect embryo implantation (Subramani et al 2016b). Due to paucibacillary nature of TB in the genital organs, conventional techniques including histology, acid-fast bacilli staining and culture tests show low-rate of positivity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations